Effect of cimetidine on gonadal function in man. - Wang, C (1982)
1 To study the effect of cimetidine on gonadal function in man, eleven male subjects with chronic duodenal ulcer were given cimetidine orally at a dosage of 1000 mg per day 3 months and 400 mg nocte for the subsequent 3 months. 2 Testosterone levels were found to be elevated during therapy when compared to pre- and post-treatment periods. Serum LH remained unchanged but FSH was increased during therapy. In five out of eleven subjects serum PRL levels were increased. Mean sperm count was lower during cimetidine therapy when compared with that after drug withdrawal. The motility and morphology of the spermatozoa were not affected.